UNUSUAL ABUNDANCE OF PSEUDOSCIAENA DIACANTHVS (LACEPEDE) OFF GOA - Dhawan, M Rajinder (Indian Journal of Fisheries, 2011)
In November 1964 and September-October 1965, the purse-seiner of the Directorate of Fisheries, Panaji (Gof), landed unusually large catches of Pseudosciaena diacanthus. The catches were dominated by fish weighing 12 to 14 kg and ranged in size 75-120 cm. The data indicate the possibility of finding new fishing ground for ’ghol’ in the deeper region along the Goa coast.